A 10-year-old child presenting with syndromic paucity of bile ducts (Alagille syndrome): a case report. (December 2016) - Pati, Girish; Singh, Ayaskanta; Nath, Preetam; Narayan, Jimmy; Padhi, Pradeep; Parida, Prasanta; Pattnaik, Kaumudee; Panda, Chittaranjan; Singh, Shivaram
Abstract Background Alagille syndrome, a rare genetic disorder with autosomal dominant transmission, manifests with five major features: paucity of interlobular bile ducts, characteristic facies, posterior embryotoxon, vertebral defects, and peripheral pulmonary stenosis. Globally, only 500 cases have so far been reported, with only five cases reported in the Indian subcontinent. Rarely, Alagille syndrome also presents with skin manifestations and early-onset chronic liver disease, which was found in our case. We believe that we report what could be the first case of Alagille syndrome presenting with café au lait spots, as no such published case report could be found in the literature. Case presentation We report an unusual case of childhood cholestatic jaundice with neonatal onset of jaundice. A 10-year-old boy from the Indian subcontinent presented with obstructive jaundice from early infancy. He also had recurrent fractures of his upper limb bones, intermittent bleeding from his nose, productive cough, decreased night vision, hyperpigmented spots over his skin, and progressive enlargement of his abdomen. Histological examination of a liver biopsy specimen revealed a paucity of bile ducts and changes suggestive of chronic liver disease. Our patient was diagnosed with Alagille syndrome and managed conservatively but died 1 year after the final diagnosis. Conclusions This particular syndromic form of paucity of bile duct disorder has been rarely reported in the Indian literature so far. Our case is notable because the child had café au lait spots and very early onset of chronic liver disease, which is quite rare in Alagille syndrome. We believe this to be the first case report on Alagille syndrome manifesting with café au lait syndrome and such early onset of chronic liver disease.